Robust view-invariant multiscale gait recognition. Issue 3 (March 2015) - Das Choudhury, Sruti; Tjahjadi, Tardi
Abstract: The paper proposes a two-phase view-invariant multiscale gait recognition method (VI-MGR) which is robust to variation in clothing and presence of a carried item. In phase 1, VI-MGR uses the entropy of the limb region of a gait energy image (GEI) to determine the matching gallery view of the probe using 2-dimensional principal component analysis and Euclidean distance classifier. In phase 2, the probe subject is compared with the matching view of the gallery subjects using multiscale shape analysis. In this phase, VI-MGR applies Gaussian filter to a GEI to generate a multiscale gait image for gradually highlighting the subject׳s inner shape characteristics to achieve insensitiveness to boundary shape alterations due to carrying conditions and clothing variation. A weighted random subspace learning based classification is used to exploit the high dimensionality of the feature space for improved identification by avoiding overlearning. Experimental analyses on public datasets demonstrate the efficacy of VI-MGR. Abstract : Highlights: The paper proposes a two-phase view-invariant multiscale gait recognition method (VI-MGR). VI-MGR is also robust to clothing variation and presence of a carried item. Phase 1 determines the matching gallery view of the probe using entropy. Phase 2 performs multiscale shape analysis using the Gaussian filter. A subject is classified using weighted random subspace learning to avoid overfitting.